Les droits de propriété sur le vivant - Geneviève Azam (Développement Durable et Territoires)
This article examines the new intellectual property rights on living organisms, which were introduced in the 1960s. These new rights break away from the idea of living organisms as common property. They bring about a radical change in human societies insofar as life and its reproduction are no longer regarded as an end in itself but exploited as means and instruments. They erase traditional boundaries between patentable invention and traditionally non-patentable discovery. The new rights henceforth apply to nature as res communis. They initiate a “Second Enclosure Movement.” But whereas fields and land can be enclosed and hedged in, rights on living organisms come under intangible property rights. Because of the specific characteristics of living organisms and given the conditions of their reproduction, intellectual property rights are clearly being extended to new areas, and corporeal and territorial rights are being questioned. Indeed, these new rights amount to controlling and appropriating the capacity to maintain and reproduce species, thereby threatening biodiversity.